The Influence of Internal and External Factors on the Successful Implementation of 5S Work Culture in Vocational Schools - Hidayat, Rizal Taufiq; Maryono, Dwi; Wardani, Dwi Esti (IJIE (Indonesian Journal of Informatics Education), 2023)
In the sphere of education, 21st-century skills are becoming increasingly important. The ability to integrate 21st-century skill competencies with workplace cultures is another requirement for vocational institutions. Many companies and industries these days are searching for employees with positive work cultures. Consequently, there is a strong and favorable correlation between workplace culture and student achievement. In addition, there is a strong correlation between students' vocational character and the 5R work culture in vocational schools. Hermawan and Nurdin's (2023) research demonstrates that the 5S work culture assessment tool achieved good content validity and reliability (0.793). Research by Balasundaram et al. (2023), applying the 5S technique can improve customer happiness, product quality, and production efficiency. Additional research by Maulidina and Wijarnaka (2023) demonstrates that work willingness is significantly and favorably impacted by the 5-person work culture by 15.90%. These three studies, however, did not examine the variables that affect the 5S work culture's successful adoption in vocational schools. The primary methodology for the research is qualitative methods; two participants complete Google forms with written interviews and observation techniques. Inductive data analysis was used to process the acquired data. The study's findings indicate that there are both internal and external elements that affect how well 5S work cultures are implemented at vocational schools. The internal factors include 1) a Well-organized curriculum; 2) well-behaved students; and 3) workload distribution. External elements, which are as follows: 1) School Persistence; 2) Industry Support; 3) Community and Parent Participation; and 4) Work Culture Integration Into Daily Practices.